New Imperialism or New Capitalism? - Jonathan Nitzan; Shimshon Bichler (Review: A Journal of the Fernand Braudel Center for the Study of Economies, Historical Systems and Civilizations, 2006)
Over the past century, the institution of capital and the process of its accumulation have been fundamentally transformed. By contrast, the theories that explain this institution and process have remained largely unchanged. The purpose of this paper is to address this mismatch. Using a broad brush, we outline a new, power theory of capital and accumulation. We use this theory to assess the changing meaning of the corporation and the capitalist state, the new ways in which capital gets accumulated and the specific historical trajectory of twentieth-century capitalism up to the present.
Keywords: 330; arms; accumulation; capital; flow; capitalism; conflict; corporation; crisis; distribution; elite; energy; finance; globalization; growth; imperialism; GPE; liberalism; Marxism; Middle East; military; national; interest; neoclassical economics; neoliberal